Temporal and spatial distribution of PM2.5 chemical composition in a coastal city of Southeast China - Li, M. R.; Min* Hu; Du, B. H.; Guo, Q. F.; Tan, T. Y.; Zheng, J.; Huang, X. F.; He, L. Y.; ZJ Wu; Guo, S. (Science of the Total Environment, 2017)
Rapid economic development and urbanization in China has been concentrated in coastal cities, resulting in haze and photochemical smog issues, especially in the densely-populated Yangtze River Delta. In this study, we explore particulate matter (specifically PM2.5) pollution in a city in Zhejiang Province (Ningbo), chosen to represent a typical, densely-populated urban city with residential and industrial sections. PM2.5 samples were collected at five sites in four seasons from Dec. 2012 to Nov. 2013. The annual average PM2.5 mass concentration was 53.2 +/- 30.4 mu g/m(3), with the highest concentration in winter and lowest in summer. Among the five sites, PM2.5 concentration was highest in an urban residential site and lowest in a suburban site, due to effects of urbanization and the anthropogenic influences. The chemical components of PM2.5 show significant seasonal variation. In addition, secondary transformation was high in Ningbo, with the highest proportion of secondary components found at a suburban site and the lowest at the industrial sites. Ningbo is controlled by five major air masses originating from inland China, from the Bohai Sea, offshore from the southeast, the Yellow Sea, and off the east coast of Korea. The relative contributions of these air masses differ, by season, with the Bohai Sea air mass dominating in winter and spring, the maritime southeast air mass in summer, and the YellowSea and coastal Korean air masses dominating in autumn. The continental air mass is associated with a high PM2.5 concentration, indicating that it is primarily transports primary emissions. In contrast, the concentration ratios among secondary formed pollutants were higher in the maritime air masses, which suggests that sea breezes control temporal and spatial variations of air pollution over coastal cities. (C) 2017 Published by Elsevier B.V.
Keywords: aerosols; Carbon; chemical components; coastal city; emissions; gasoline; motor-vehicles; origins; pm10; pm2.5; secondary formation; temporal and spatial distribution; Transport